2016
DOI: 10.1088/1674-1056/25/5/054206
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of melt ejection during long pulsed laser drilling

Abstract: In pulsed laser drilling, melt ejection greatly influences the keyhole shape and its quality as well, but its mechanism has not been well understood. In this paper, numerical simulation and experimental investigations based on 304 stainless steel and aluminum targets are performed to study the effects of material parameters on melt ejection. The numerical method is employed to predict the temperatures, velocity fields in the solid, liquid, and vapour front, and melt pool dynamics of targets as well. The experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 47 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…and βr is the retro-diffusion coefficient assumed to be 0 at the beginning of evaporation, while 1 at steady state [25]. ρ is the mixture density [kg/m 3 ], l ρ is the liquid density [kg/m 3 ], δ(φ) is the delta function, and φ is the level-set function.…”
Section: Mathematical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…and βr is the retro-diffusion coefficient assumed to be 0 at the beginning of evaporation, while 1 at steady state [25]. ρ is the mixture density [kg/m 3 ], l ρ is the liquid density [kg/m 3 ], δ(φ) is the delta function, and φ is the level-set function.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…K is the isotropic permeability in a porous medium model [2], describing the solid/liquid phase-change process. F is the gas/liquid interface force [N], including surface tension, recoil pressure, and Marangoni force [25], which mainly influences the properties of the fluid flow in the melt pool.…”
Section: Mathematical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the previous work in Ref. [34], for the isotropic PBG reservoir, the Green's functions can be expressed as…”
Section: Equations For the Absorption And Dispersion Spectramentioning
confidence: 99%
“…Zhang et al found that the density of states of photonic crystal determined the relative height of the middle peak in the spontaneous emission spectrum of Λ-type and V-type three-level atoms. [22] It made a two-peak structure with wide dark lines appearing in the spontaneous emission spectrum of Λ type three-level atom which located at the defect position in the defect photonic crystal. [23] In the presence of the driving field and defect mode, the nature of quantum interference was depended on the initial atomic coherence.…”
Section: Introductionmentioning
confidence: 99%